Break Time Exchanges: Social Construction of “Resting” Spaces Among the Vietnamese-Czech Community in Sapa, in Prague - Nguyen, Quynh (Lidé města, 2021)
This study provides a snapshot of the social lives of primarily first-generation Vietnamese-Czech immigrants, who engage in small-scale merchant business at the Sapa market and cultural centre in Prague. To add to the existing research on the Vietnamese immigrant community in the Czech Republic, the research shifts from studying the immigrant community’s identity as business owners to their identities as cultural participants by observing the community’s interactions during break times. The researcher utilizes the framework of spatializing culture to focus on how such interactions help socially construct and transform the resting spaces, existing in both the physical and online worlds of the Sapa market and cultural space. This ethnographic study combines participant observation, insider ethnography, visual mapping, and visual and digital ethnography. The fieldwork reveals that the physical and digital rest areas of Sapa help facilitate ethnic identity construction and preservation among the community members.